Comparative legal analysis of the legislation on artificial termination of pregnancy of ukraine and foreign countries - Detuikova, K. D. (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. To carry out a comparative legal analysis of the norms governing abortion in Ukraine and the world.
Keywords: тези доповідей